2005
DOI: 10.1093/rpd/nch471
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity in building materials used in and around Dhaka city

Abstract: The activity levels of (226)Ra, (232)Th and (40)K were determined using gamma-ray spectroscopy in different commercial brands of cement, sand and hollow concrete bricks, which were collected from the building material suppliers of Dhaka City. The activity concentrations in the samples were found to be somewhat higher than in other countries. An effort has been made to assess the radiation hazard associated with these materials by determining the gamma activity concentration index I. It was found that the value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Although number of studies of NORM have been performed in Bangladesh for conventional building materials such as brick, sand, cement, gravel, gypsum, limestone and powdered lime, [8][9][10] information on the content of radioactivity from decorative building materials like granites, clay tiles and mosaic stone, etc. and their associated radiological hazards are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although number of studies of NORM have been performed in Bangladesh for conventional building materials such as brick, sand, cement, gravel, gypsum, limestone and powdered lime, [8][9][10] information on the content of radioactivity from decorative building materials like granites, clay tiles and mosaic stone, etc. and their associated radiological hazards are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the natural radioactivity levels in building materials is not only needed to assess the possible radiological hazards to human health but also to develop standards and guidelines for the use and management of these materials. 1 In recent years, there has been an increasing interest in the study of the radioactivity in various building materials, 225 although there are a few studies on the radioactivity of building materials used. Some cities in Turkey 2629 require detailed information of the activity concentrations of 226 Ra, 232 Th and 40 K in building materials used but these are not available in literature.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a great attention has been paid to determining radionuclide concentrations in building materials in many countries [3] [9]- [19]. However, for Bangladesh, there is only a few experimental data [7] [20] [21] [22] available in literature regarding the radioactivity of building materials. Mollah et al [20] found a somewhat higher level of activity in building materials than in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The activity levels in brick samples were found to be consistent with some of that reported in literature. Recently, Asaduzzaman et al [7] and Roy et al [22] investigated some building materials (brick, sand and cement). The aim of the present research is not only the determination of natural radioactivity in some building materials but also the evaluation of the radiological hazard parameters such as Ra eq , D, D eff , H ex , H in , I γ , I α , AGDE and ELCR.…”
Section: Introductionmentioning
confidence: 99%